2022
DOI: 10.1186/s11556-022-00299-9
|View full text |Cite
|
Sign up to set email alerts
|

The effects of interventions to enhance cognitive and physical functions in older people with cognitive frailty: a systematic review and meta-analysis

Abstract: Introduction Cognitive frailty is the co-existence of mild cognitive impairment and physical frailty that increases the risk of adverse health outcomes. The existing systematic reviews on cognitive frailty in the literature have focused only on identifying associated factors and adverse outcomes, and their relationship with frailty and cognition. This study aimed to examine the effects of interventions on cognitive functions, frailty, and physical functions and provide an overview of interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…The included studies' aerobic exercises utilized Tai Chi Chuan 53 which benefits both frailty and cognition. Research suggests that physical exercises should be an essential component of CF intervention 20 . Moreover, aerobic exercise specifically helps frail seniors with depression and anxiety 61 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The included studies' aerobic exercises utilized Tai Chi Chuan 53 which benefits both frailty and cognition. Research suggests that physical exercises should be an essential component of CF intervention 20 . Moreover, aerobic exercise specifically helps frail seniors with depression and anxiety 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that physical exercises should be an essential component of CF intervention. 20 Moreover, aerobic exercise specifically helps frail seniors with depression and anxiety. 61 prevention is key to avoiding irreversible dementia.…”
Section: Gradementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, VR and AR can also be applied to other domains, such as the behavioral domain in combination with other domains or separately to offer older adults real time management and make the consequences of their behaviors more tangible to motivate them to change. 137 , 138 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, VR and AR can also be applied to other domains, such as the behavioral domain in combination with other domains or separately to offer older adults real time management and make the consequences of their behaviors more tangible to motivate them to change. 137,138 From the intended purpose perspective, this review concluded that VR training and rehabilitation appeared to be a promising supplement, if not an alternative, to traditional physiotherapy techniques. However, older adults are often hesitant to adopt training or rehabilitation without assistance, this may be due to their limited familiarity with technological advances.…”
Section: Social Well-beingmentioning
confidence: 99%